2005
DOI: 10.1029/2004gl021685
|View full text |Cite
|
Sign up to set email alerts
|

Long duration meteor echoes characterized by Doppler spectrum bifurcation

Abstract: [1] We report on a new category of long lasting meteor echoes observed occasionally with HF and VHF radars. These meteoric returns, which have lifetimes from many seconds to a few minutes, are characterized by a distinct Doppler spectral signature showing a pronounced Doppler bifurcation which includes narrow bands of discrete Doppler velocities, often of opposite polarity. The large signal to noise ratios and the narrowness of the spectra imply that coherent or Bragg scattering is not of relevance here, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 12 publications
5
20
0
Order By: Relevance
“…It was found that the drifts of trail irregularity have an obvious shear from 50 ms -1 to -50 ms -1 . The shear structure of the winds observed in this study reminds us of suggestions made by Bourdillon et al [7] that the structured wind shear drives parts of the trail plasma in a way similar to the process responsible for the formation of sporadic E layer, and sustains the trail for a long time. In this context, the cause responsible for the structural evolution of trail irregularity from the initially formed strip-type to layer-type could be linked with the neutral wind effect.…”
Section: Discussion and Summarysupporting
confidence: 86%
See 2 more Smart Citations
“…It was found that the drifts of trail irregularity have an obvious shear from 50 ms -1 to -50 ms -1 . The shear structure of the winds observed in this study reminds us of suggestions made by Bourdillon et al [7] that the structured wind shear drives parts of the trail plasma in a way similar to the process responsible for the formation of sporadic E layer, and sustains the trail for a long time. In this context, the cause responsible for the structural evolution of trail irregularity from the initially formed strip-type to layer-type could be linked with the neutral wind effect.…”
Section: Discussion and Summarysupporting
confidence: 86%
“…On the other hand, it is known that the durations of meteor trail at different altitudes are dictated primarily by the external electric field/wind, diffusion rate and the polarization of meter trail as a function of altitude [6]. In particular, on the basis of the Doppler spectral bifurcation or Doppler velocity shear characteristics associated with long duration RSTEs, the neutral wind shear has been suggested to be a possible candidate to account for the observed long duration RSTEs at a specific altitude [7,10]. By taking a similar way as Li et al [5], the drifts of trail irregularity associated with the long duration RSTEs were obtained.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the signal strength depends on the inverse-cube of the distance to the meteor, there should be many very bright nearby RFI sources on the horizon but these are not observed. This pattern is also inconsistent with non-specular reflections, which are preferentially located in a relatively small region of the sky that satisfies the requirement that the pointing vector is perpendicular to the geomagnetic field (Bourdillon et al 2005;Close et al 2011). For these reasons it seems unlikely that forward scattering is responsible for the signals detected from fireballs.…”
Section: Resultsmentioning
confidence: 95%
“…The observed transients are also inconsistent with light curves from non-specular echoes, which vary greatly from one to the next, following no particular pattern. More importantly, however, non-specular echoes are weaker and more rare than over-dense specular echoes (Bourdillon et al 2005;Close et al 2011). Therefore if the LWA1 were seeing non-specular reflections it should also see many more bright specular reflections scattering from the same transmitters.…”
Section: Resultsmentioning
confidence: 99%